Towards a successful implementation Business Process Management (BPM) for sustainable organization performance. - Wong , Wai Peng (Universiti Sains Malaysia, 2015)
This study has examined the factors that affect the implementation of Business Process Management (BPM) as well as the impact of BPM on organizations performance in Malaysia. Manufacturing and service firms have been our focus in this research because these sectors contributes largely to the Gross Domestics Products (GDP) of Malaysia. Our research findings reveal that the business environment affects the business process adoption in Malaysia. Internal factor which is strategy influences business process adoption. Following that, this research also found that the extent of business process implmementation affects the organization performance. The contribution of this research is a framework that characterizes business process management and its impact on organization performance.